2014
DOI: 10.1542/hpeds.2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Resource Utilization of Pediatric Patients Exposed to Venom

Abstract: BACKGROUND AND OBJECTIVE:Treating envenomation with antivenom is costly. Many patients being treated with antivenom are in observation status, a billing designation for patients considered to need care that is less resourceintensive, and less expensive, than inpatient care. Observation status is also associated with lower hospital reimbursements and higher patient cost-sharing. The goal of this study was to examine resource utilization for treatment of envenomation under observation and inpatient status, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… Mean income loss: US$93. Expenditure for venomous snakebite: US$231 Expenditure non-venomous snakebite: US$34 Saz-Parkinson et al (2012) Spain Mean: Euro2000 per case Narra et al (2014) 33 children's Hospitals in Pediatric Health Information System, USA Patients receiving anti-venom under observation status: US$17665 In-patients receiving anti-venom: US$20503 Kasturiratne et al (2017) Sri Lanka Annual estimated health system cost: US$10,260,651.53 Cost of anti-venom: US$6.3 million Cost of hospital care: US$3.9 million Tochie (2017) Cameroon Cost of an AVS vial: US$67–75 or US$20–23 Okumu et al, 2019 JOOTRH, Kisumu County, Western Kenya The median cost of treating snakebite: 2652 KES (US$26). Magalhães et al (2020) Brazilian Amazon Health system cost: US$3.115.861,28.…”
Section: Resultsmentioning
confidence: 99%
“… Mean income loss: US$93. Expenditure for venomous snakebite: US$231 Expenditure non-venomous snakebite: US$34 Saz-Parkinson et al (2012) Spain Mean: Euro2000 per case Narra et al (2014) 33 children's Hospitals in Pediatric Health Information System, USA Patients receiving anti-venom under observation status: US$17665 In-patients receiving anti-venom: US$20503 Kasturiratne et al (2017) Sri Lanka Annual estimated health system cost: US$10,260,651.53 Cost of anti-venom: US$6.3 million Cost of hospital care: US$3.9 million Tochie (2017) Cameroon Cost of an AVS vial: US$67–75 or US$20–23 Okumu et al, 2019 JOOTRH, Kisumu County, Western Kenya The median cost of treating snakebite: 2652 KES (US$26). Magalhães et al (2020) Brazilian Amazon Health system cost: US$3.115.861,28.…”
Section: Resultsmentioning
confidence: 99%
“…A study in 2009 found mean charges of more than $17,000 for pediatric patients with snakebite injuries who were treated with antivenom. 30 In that study, 32% of patients received antivenom. Although we do not know how many patients in our study received antivenom and cannot differentiate charges based upon treatment, it is likely that antivenom use at least partially accounts for the higher costs of ED visits for snakebites compared with nonsnakebite visits.…”
Section: Resultsmentioning
confidence: 88%
“…Interestingly, coverage by Medicaid was more common for both age groups among children seen in the ED for a diagnosis other than snakebite than for snakebites. A study in 2009 found mean charges of more than $17,000 for pediatric patients with snakebite injuries who were treated with antivenom 30 . In that study, 32% of patients received antivenom.…”
Section: Discussionmentioning
confidence: 95%
“…If less severe bites are treated with antivenom, this may lead to an increase in hospital admission and possibly increased cost for these patients. 34 This is relevant in the setting of increasing concerns about healthcare costs and emergency department boarding. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…If less severe bites are treated with antivenom, this may lead to an increase in hospital admission and possibly increased cost for these patients. 34 This is relevant in the setting of increasing concerns about healthcare costs and emergency department boarding. 35,36 Future studies should evaluate antivenom use across the United States as more studies are published and the current studies become more disseminated into standard emergency medicine and toxicology practice.…”
Section: Discussionmentioning
confidence: 99%